The Properties of the ‘Ospedale Maggiore’ of Milan in the Lodigiano in the Second Half of the 15th Century: Economic Management and Seignorial Rights (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
This paper focuses on a peculiar type of rural lordship. The analysis of the forms by which the Lodi estates were managed in the 15th century, after being handed over to the Ospedale Maggiore of Milan, clearly shows that the hospital’s Chapter reactivated and renewed seigneurial bonds. The control over peasants is visible in the appointment of the podestà (entrusted with various tasks: estate management, justice, etc). This official exercised a strict control over farming activities, in an area affected by significant agricultural transformations at the end of the Middle Ages.
Keywords: Ospedale Maggiore; Milan; seignorial rights; Lodi; land management